Review of Oribotritia (Acari, Oribatida, Oribotritiidae) with a world checklist and description of a new species from China - Liu, Dong (Zootaxa, 2015)
The oribatid mite genus Oribotritia Jacot, 1924 (Oribotritiidae) is reviewed. A new species of Oribotritia collected from litter in Hunchun, China, Oribotritia hunchunensis sp. nov., is described and figured. Four species, Oribotritia angusta Mahunka, 1982, Oribotritia asiatica Hammer, 1977, Oribotritia chichijimensis Aoki, 1980, Oribotritia gigas Bayoumi & Mahunka, 1979, are redescribed based on Chinese specimens. Oribotritia nepalensis Niedbała, 2000 is considered as a new junior subjective synonym of Oribotritia gigas Bayoumi & Mahunka, 1979. A comprehensive, fully annotated and referenced checklist of all known species and a key to known Chinese species of this genus are provided to facilitate to the further research.